2008
DOI: 10.1002/hbm.20626
|View full text |Cite
|
Sign up to set email alerts
|

The Fusiform Face Area responds automatically to statistical regularities optimal for face categorization

Abstract: Statistical regularities pervade our perceptual world. Assuming that the human brain is tuned for satisfying the constraints of the visual environment, visual system computations should be optimized for processing such regularities. A socially relevant and highly recurrent homogenous pattern for which the brain has developed sensitivity is certainly the human face. Yet, for which statistical regularities the face sensitive regions are tuned for, and to what extent their detection occurs automatically is largel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 46 publications
3
33
0
1
Order By: Relevance
“…When this factor is controlled, the apparent bias for the upper part of words vanishes completely, as we revealed in Experiment 2. Hence, the bias for the upper part of objects that occurs in the visual perception of particular features in faces (e.g., Caldara & Seghier, 2009) and objects (Thomas & Elias, 2011) does not seem to affect the automatic detection of letter features during visual-word recognition.…”
Section: Discussionmentioning
confidence: 99%
“…When this factor is controlled, the apparent bias for the upper part of words vanishes completely, as we revealed in Experiment 2. Hence, the bias for the upper part of objects that occurs in the visual perception of particular features in faces (e.g., Caldara & Seghier, 2009) and objects (Thomas & Elias, 2011) does not seem to affect the automatic detection of letter features during visual-word recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The right hemisphere has been long considered predominant for human face recognition [Levy et al, 1972;Rhodes, 1985]. The asymmetrical processing of human faces is often attributed to the role played by the right hemisphere in global or holistic processing [Jiang et al, 2009; as well as its sensitivity to specific stimulus regularities that characterize human faces [Caldara and Seghier, 2009]. This right hemisphere dominance is further supported by patient studies showing that deprivation of visual information to the right hemisphere results in face recognition impairment, but not so in left hemisphere deprivation [Le Grand et al, 2003] and that acquired prosopagnosia is most often caused by lesions to the right (or bilateral) cortex [Barton et al, 2002;De Renzi, 1997;Rossion, 2008;.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging findings have shown that brain regions dedicated to face processing are tuned to process intrinsic visual regularities present in human faces (i.e., a topheavy vertical bias constituted by the eyes, eyebrows, hairs toward the mouth). Neurons in the right middle fusiform gyrus respond to non-face curvilinear shapes containing more high-contrast elements in the upper compared to the lower part (Caldara & Seghier, 2009;Caldara et al, 2006), indicating that such low-level global properties might be used by those neurons to automatically categorize visual shapes as human faces.…”
Section: Discussionmentioning
confidence: 99%